STRATEGI PENINGKATAN DAYA SAING INDUSTRI FURNITURE ROTAN INDONESIA DI KAWASAN ASEAN DAN TIONGKOK - Rudi Eko Setyawan; Henny K Daryanto; Rina Oktaviani (School of Business, Bogor Agricultural University (SB-IPB), 2016)
Competitiveness of a country’s export commodities is one of the indicators used to measure its economic progress. This study aims to analyze the competitiveness of Indonesian rattan furniture in China and the ASEAN region, along with the influencing factors and to conclude appropriate strategies to improve its competitiveness. The analysis was conducted by utilizing Diamond's Porter, Normalized Revealed Comparative Advantage (NRCA), and panel data regression. The results showed that the competitiveness of Indonesian rattan furniture in the ASEAN region and China, in the period of 2001 to 2014, is fluctuated with small level of competitiveness. This notion can be seen from all of the positive NRCA index values. In the Fixed Effects Model (FEM), the independent variables that significantly influence NRCA include the export prices and volumes, global prices of rattan furniture and raw rattan, the number of rattan industries, production of real rattan, production value of rattan, investment of rattan industry, direct labor of rattan industry, interest rate of Bank loans, implementation of ACFTA and violation policy of raw and semi-finished rattan exports. To increase the competitiveness of Indonesian rattan furniture, the government is urged to establish a development or training center for the innovative designs and improvement of quality standard of Indonesian rattan furniture. This is also supported by a guarantee of rattan raw material availability and technological improvement of rattan processing industry. Thus, the third step to perform is the improvement of infrastructure and distribution chain, improvement of market information systems, and strengthening of brand image of rattan furniture in Indonesia.Keywords: competitiveness of rattan furniture, diamond's porter, normalized revealed comparative advantage, fixed effect model ABSTRAKDaya saing komoditas ekspor negara merupakan salah satu indikator yang digunakan untuk mengukur kemajuan ekonomi suatu negara. Penelitian ini bertujuan untuk menganalisis daya saing furniture rotan Indonesia di kawasan ASEAN Tiongkok serta faktor-faktor yang memengaruhinya dan kemudian menyimpulkan strategi yang tepat untuk meningkatkan daya saingnya. Analisis dilakukan dengan menggunakan Diamond’s Porter, Normalized Revealed Comparative Advantage (NRCA) dan regresi data panel. Hasil penelitian menunjukkan bahwa daya saing furniture rotan Indonesia di kawasan ASEAN dan Tiongkok dalam kurun waktu 2001 hingga 2014 berfluktuasi dan sebenarnya masih mempunyai daya saing meskipun kecil, hal ini dapat dilihat dari semua nilai indeks NRCA nilainya positif. Pada Fixed Effect Model (FEM), variabel independen yang berpengaruh signifikan terhadap NRCA adalah harga ekspor, volume ekspor, harga furniture rotan dunia, harga rotan mentah dunia, jumlah perusahaan industri rotan di Indonesia, produksi rotan riil di Indonesia, nilai produksi rotan di Indonesia, investasi industri rotan di Indonesia, tenaga kerja langsung industri rotan, besarnya suku bunga pinjaman Bank, pemberlakuan ACFTA dan kebijakan pelarangan ekspor rotan mentah maupun setengah jadi. Untuk mampu meningkatkan daya saing furniture rotan Indonesia, pemerintah harus mendirikan pusat pengembangan atau pelatihan dan pengembangan desain yang inovatif maupun standart mutu furniture rotan Indonesia. Hal ini juga didukung dengan adanya jaminan ketersediaan bahan baku rotan dan peningkatan teknologi industri pengolahan rotan. Hal ketiga yang perlu dilakukan adalah perbaikan infrastruktur maupun rantai distribusi, perbaikan sistem informasi pasar rotan serta penguatan brand image furniture rotan Indonesia.Kata Kunci: daya saing furniture rotan, diamond’s porter, normalized revealed comparative advantage, fixed effect model